Virtual screening of Kocuria oceani AT-1 metabolites as potential maize growth regulators under drought conditions using molecular docking and dynamics simulation - Muhammad Usama; Mahwish Salman; Ghulam Mustafa (PLoS ONE, 2026)
Maize is a vital cereal crop, severely affected by environmental factors and climate change. Among abiotic factors, drought stress is considered one of the most detrimental factors limiting plant growth and biomass production. However, the molecular basis of bacterial metabolite-mediated drought tolerance in cereal crops remains poorly understood. The current in silico study aimed to investigate the molecular interactions between Kocuria oceani AT-1 metabolites and the maize UGT706F8 protein, using molecular docking and dynamics simulation analyses. The molecular interactions between bacterial metabolites and the UGT706F8 protein (glycosyltransferase enzyme, PDB ID 7Q3S) from Zea mays L. were evaluated. The in silico docking findings revealed a favorable binding affinity between bacterial metabolites and the target protein, indicating stable molecular interactions at the protein active site. Specifically, 4-tetradecanoyl-2,6-piperazinedione, and 3-benzylhexahydropyrrolo(1,2-a)pyrazine-1,4-dione displayed binding energies of −7.5 ± 0.33 and −8.5 ± 0.36 kcal/mol against the target protein, respectively. Under identical docking parameters, the known plant growth regulators (indole acetic acid and abscisic acid) yielded binding energies of −6.6 ± 0.34 and −5.8 ± 0.32 kcal/mol, respectively. Re-docking of the native uridine-5-diphosphate (UDP) ligand yielded a Root Mean Square Deviation (RMSD) of 0.9 Å, validating the reliability of the docking procedure. Additionally, molecular dynamics simulation (200 nanoseconds) outcomes supported these predictions, indicating stable molecular interactions and structural integrity of ligand-protein complexes, with ligand RMSD values remaining between 2 and 3 Å. The formation of hydrogen bonding (an average of 2.4 ± 0.6 and 2.1 ± 0.5, respectively), hydrophobic interactions, and stable Solvent-Accessible Surface Area (SASA) profiles (ranging between 19,000–22,000 Å 2 and 19,000–21,000 Å 2 , respectively) suggest the stability of complexes. Moreover, Molecular Mechanics Generalized Born Surface Area (MM-GBSA) outcomes (−102.05 ± 13.96 and −54.86 ± 7.93 kcal/mol, respectively) supported the favorable binding energetics of ligand-protein complexes. These computational outcomes suggest that Kocuria oceani metabolites can establish stable molecular interactions with the UGT706F8 protein, which may influence glycosyltransferase function. Further in vivo experimental validation is required to confirm their predicted maize growth-promoting potential under drought conditions.